Strengthening Public Sector Integrity through Good Corporate Governance: Insights from Bibliometric Analysis and Literature Review - Gunawan, William Ben; Setyaningsih, Putri Anggraini; Rahmawati, Nisa; Rahman, Abdu (Inspektorat Kabupaten Majalengka, 2025)
Research on GCG has expanded significantly due to growing public scrutiny, the demand for accountability, and the recognition that governance quality shapes institutional integrity. This study explores the evolving landscape of research on GCG through a bibliometric analysis and literature review. Using data extracted from Scopus and visualized via VOSviewer, keyword mapping identifies GCG as the central theme, frequently associated with financial performance, firm value, corporate social responsibility, earnings management, and audit committees. Overlay visualization indicates a shift in focus from traditional financial metrics toward broader governance dimensions, including transparency and stakeholder engagement. These findings suggest that the discourse around GCG has matured beyond its financial roots to encompass ethical and institutional perspectives. Thus, this paper serves as a reference point for academics, practitioners, and policymakers seeking to enhance governance frameworks in private and public institutions. Future research should employ multi-method approaches to investigate causal relationships and contextual differences.